Scottish local government - McConnell, Allan, 1957- (Edinburgh University Press, 2004)
This book provides academics, students, practitioners, journalists and others with a broad-ranging yet detailed account, not just of how local government actually works, but also the main political issues and debates surrounding its multi-faceted roles in contemporary Scotland.